INFLAMMATORY EFFECT OF ANTIBIOTIC-KILLE STAPHYLOCOCCUS XYLOSUS ON MURINE RENAL SYSTEM - Al-Mathkhury, Harith; Rhumaid, Abdulkadir (Iraqi Journal of Science, 2024)
One hundred and fifty urine specimens were collected from patients with urinary tract infection, visiting Alyarmouk, Alkarama, and Madinat Altib hospitals in Baghdad. Staphylococci were isolated from 51 urine specimens, 39 isolates were coagulase-negative Staphylococci. Seven isolates (4.5%) were identified as Staphylococcus xylosus. Most of isolates are multiresistant to more than one antibiotic; all the isolates were susceptible to ciprofloxacin, and resistant to erythromycin, the isolate S. xylosus S4 was elected because of its susceptibility to more than one antibiotic. In order to testify the pathogenicity of antibiotics-killed S. xylosus S4 in murine urinary tract system, mice were injected with S. xylosus S4 supernatant which previously exposed to Ampicillin, Cefotaxime, Gentamicin, Rifampin, Erythromycin, Co-Trimoxazole, or Ciprofloxacin at concentration of 200, 600, 200, 100, 300, 100, 500 μg / 0.2 ml respectively via intraurethral catheter. Organs of mice (kidneys and bladders) treated with beta-lactam-killed S. xylosus S4 showed different pathological changes in kidneys included infiltration of inflammatory cells, haemorrhage and vaculation of blood vessels, whereas the bladders developed dekeratinazation and infiltration of inflammatory cells. However, kidneys and bladders maintained normal state after exposure to supernatant of S. xylosus S4 with antibiotics other than beta-lactam.